Construction of a hybrid electrical racing kart as a student project - Knoke, Tobias; Schneider, Tobias; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Optimal Power Train Design of a Hybrid Refuse Collector Vehicle - Knoke, Tobias; Böcker, Joachim (2007 IEEE Vehicle Power and Propulsion Conference)

Implementation of dynamically reconfigurable control structures on a single FPGA platform - Mathapati, Shashidhar; Böcker, Joachim (2007 European Conference on Power Electronics and Applications)

Logik als Ethik des Denkens: Der Tübinger Philosoph Christoph Sigwart (1830-1904) und die Logik des 19. Jahrhunderts - Peckhaus, Volker (Methodisches Denken im Kontext. Festschrift für Christian Thiel. Mit einem unveröffentlichten Brief Gottlob Freges)

W. R. Hamilton (1805–1865) - Peckhaus, Volker (Handbook of Whiteheadian Process Thought)

Logic and Metaphysics: Heinrich Scholz and the Scientific World View - Peckhaus, Volker (Philosophia Mathematica)
Abstract: Zbl. Math. 1144.03003 (Reinhard Kahle).

Paralleling of LLC resonant converters using frequency controlled current balancing - Figge, H.; Grote, T.; Froehleke, N.; Boecker, J.; Ide, P. (2008 IEEE Power Electronics Specialists Conference)

LLCC-PWM inverter for driving high-power piezoelectric actuators - Li, R.; Fröhleke, N.; Böcker, Joachim (13th International Power Electronics and Motion Control Conference, Poznan, Poland)

Linear switched reluctance motor as a high efficiency propulsion system for railway vehicles - Kolomeitsev, L.; Kraynov, D.; Pakhomin, S.; Rednov, F.; Kallenbach, E.; Kireev, V.; Schneider, T.; Böcker, Joachim (2008 International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

System Architecture and Risk Management for Autonomous Railway Convoys - Henke, Christian; Tichy, Matthias; Schneider, Tobias; Böcker, Joachim; Schäfer, Wilhelm (2008 2nd Annual IEEE Systems Conference)

Analysis and Design of a Novel Three-Level LLCC Inverter Supplying an Airborne Piezoelectric Brake Actuator - Li, Rongyuan; Fröhleke, Norbert; Böcker, Joachim (2007 IEEE Power Electronics Specialists Conference)

Design of Power Supply for Driving High Power Piezoelectric Actuators - Li, Rongyuan; Lönneker, Michael; Fröhleke, Norbert; Böcker, Joachim (2008 IEEE Industry Applications Society Annual Meeting)

Die Zeitschrift für die Grundlagen der gesamten Mathematik. Ein gescheitertes Zeitschriftenprojekt aus dem Jahre 1908 - Peckhaus, Volker (Publikationsstrategien einer Disziplin. Mathematik in Kaiserreich und Weimarer Republik)

Fixing Cantor’s Paradise: The Prehistory of Ernst Zermelo’s Axiomatization of Set: Theory - Peckhaus, Volker (New Approaches to Classes and Concepts)
Rezension: MR 2777837 (2012a:03003, J. Dawson).

¿Adiós Descartes? Una rehabilitación pragmática del racionalismo - Peckhaus, Volker (Filosofía y historia de la ciencia en el Cono Sur)

Anthropologismus als ‚guter Psychologismus‘, erweiterte Stellungnahme zu Christoph Sigwart, „Die Zahlbegriffe“ (1904) - Peckhaus, Volker (Erwägen, Wissen, Ethik)

Zu Christoph Sigwarts ‚Die Zahlbegriffe‘, Ausgangsstellungnahme zu Christoph Sigwart, „Die Zahlbegriffe“ (1904) - Peckhaus, Volker (Erwägen, Wissen, Ethik)

Control of a linear switched reluctance motor as a propulsion system for autonomous railway vehicles - Kolomeitsev, L.; Kraynov, D.; Pakhomin, S.; Rednov, F.; Kallenbach, E.; Kireev, V.; Schneider, T.; Böcker, Joachim (2008 13th International Power Electronics and Motion Control Conference)

Galois, Évariste - Peckhaus, Volker; v. Bülow, Christopher (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Frege, Friedrich Ludwig Gottlob - Peckhaus, Volker (New Dictionary of Scientific Biography, 8 Bde., Bd. 3: Fairey–Hypatia)

Gregory, Duncan Farquharson - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Grellingsche Antinomie - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Graßmann, Robert - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Genidentität - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Hermes, Hans - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 3: G–Inn)

Taking Fingerprints of Speech-And-Gesture Ensembles. Approaching Empirical Evidence of Intrapersonal Alignment in Multimodal Communication - Lücking, Andy; Mehler, Alexander; Menke, Peter (Proceedings of 12th Workshop on Semantics and Pragmatics of Dialogue)

Simon Blackburn, The Oxford Dictionary of Philosophy, second edition. Oxford: Oxford University Press, 2005 - Peckhaus, Volker (History and Philosophy of Logic)

Johann Heinrich Lambert. Philosophische Schriften. Vol. VIII: Kleinere philosophische Abhandlungen und Rezensionen. Edited by A. Emmel and A. Spree, Georg Olms Verlag, Hildesheim, Zurich and New York 2007, Part 1, Part 2 - Peckhaus, Volker (Bulletin of Symbolic Logic)

Special Issue: Leopold Löwenheim (1878-1957). Edited by C. Thiel, History and Philosophy of Logic, vol. 28, no. 4 (November 2007). Taylor & Francis, Abingdon, Oxon, UK, pp. 289–336 - Peckhaus, Volker (Bulletin of Symbolic Logic)

Grußwort des Dekans der Fakultät für Kulturwissenschaften - Peckhaus, Volker (Verabschiedung Prof. Dr. Wolfgang Keim)

VIRTEX – Lehr- und Lernmaterialien für den Fachsprachenunterricht in Hotel und Gastronomie - Ballweg, Sandra (Auf neuen Wegen. Deutsch als Fremdsprache in Forschung und Praxis. Tagungsband der 35. Jahrestagung des Fachverbandes Deutsch als Fremdsprache 2007 an der Freien Universität Berlin)

„Wann ist die nächste Sprechstunde?“ Betreuung und Beratung im Online Writing Lab - Ballweg, Sandra (Zeitschrift für Interkulturellen Fremdsprachenunterricht 13/11)

Schreiben lernen von Anfang an – Schreibförderung in Integrationskursen - Ballweg, Sandra (Deutsch als Zweitsprache 2)

DaF-Lehrende und das Europäische Sprachenportfolio - Stork, Antje; Ballweg, Sandra (InfoDaF4)

Regressionsanalyse - Kraft, Manfred; Lück, Sonja (Enzyklopädie der Wirtschaftsinformatik - Online-Lexikon)

Statistik - Kraft, Manfred; Lück, Sonja (Enzyklopädie der Wirtschaftsinformatik - Online-Lexikon)

Wilholt, Torsten, "Zahl und Wirklichkeit. Eine philosophische Untersuchung über die Anwendbarkeit der Mathematik", mentis Verlag: Paderborn 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hauser, Kai, “Gödel’s Program Revisited. I: The Turn to Phenomenology”, In: Bulletin of Symbolic Logic 12 (2006), 529–590 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lorenz, Kuno, “Logic as Tool of Science versus Logic as a Scientific Subject”, in: Johan van Benthem et al. (eds.), The Age of Alternative Logics. Assessing Philosophy of Logic and Mathematics Today. Based on the Conference on Philosophical Insights into Logic and Mathematics, Nancy, France, September 30–October 4, 2002, Dordrecht: Springer 2006, 299–310 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Vidal-Rosset, Joseph, “Does Gödel’s Incompleteness Theorem Prove that Truth Transcends Proof”, in: van Bentham et al. (eds.), The Age of Alternative Logics. Assessing Philosophy of Logic and Mathematics Today, Dordrecht: Springer 2006, 51–73 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "On the Mathematical Method and Correspondence with Exner", transl. by Paul Rusnock/Rolf George, Amsterdam: Rodopi (Studien zur Österreichischen Philosophie; 37) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bueno, Otávio/Zalta, Edward N., “A Nominalist’s Dilemma and its Solution”, In: Philosophia Mathematica (3) 13 (2005), 294-307 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ekeland, Ivar, "The Best of All Possible Worlds. Mathematics nd Destiny", University of Chicago Press: Chicago, IL 2006 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Leng, Mary, “Revolutionary Fictionalism: A Call to Arms”, In: Philosophia Mathematica (3) 13 (2005), 277–293 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mancosu, Paolo, “Mathematical Explanation: Problems and Prospects”, In: Topoi 20 (2001), 97–117 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Fachspezifische Sprachförderung im Rahmen einer beruflichen Ersatzmaßnahme; bwp@ Berufs- und Wirtschaftspädagogik - online, Ausgabe bwp@ Spezial 4 - HT2008 - Niederhaus, Constanze

AlphaZ Evaluation. Sachbericht 2007 - Badel, Steffi; Niederhaus, Constanze

Job Fit Deutsch. Berufseinstiegsjahr; Baden-Württemberg - Dornhöfer-Oßwald, Gisela; Niederhaus, Constanze; Nowak, Klaus

Arbeitsblätter für den fachsprachlichen Deutschunterricht im Fach Elektrotechnik am Shanghai Hamburg College - Herrmann, Barbara; Niederhaus, Constanze; Parádi, Zsuzsa; Sebestyén, Katalin

Sprachen im Konflikt: Zur diskursiven Reflexion der Galizischen Polyglossie in Lemberger Zeitungen des ausgehenden 19. Jahrhunderts - Ptashnyk, Stefaniya (Deutsch in multilingualen Stadtzentren Mittel- und Osteuropas. Um die Jahrhundert-wende vom 19. zum 20. Jahrhundert)